The Evolution of the Idea of Security Community in Innternational Relations - Ruhollah Talebi Arani; Farhaad vafaeifard (رهیافتهای سیاسی و بین المللی)
Since its inception, social science in general and international relations in particular have always focused on collective human entities. In the meantime, various concepts have been used to refer to these collective entities; One of which is security community, coined by Deutsch and his colleagues proposed for the first time in 1957. From the 1950s, this concept has been a theoretical basis for many scholars to explain international developments, but over time it has been reformulated; This article tries to evaluate the position of this concept in the literature of international relations with a critical view by using the content analysis of the theoretical texts that have been written about the security community in the last six decades. The question is, what is the evolution of the security community since its inception? The findings of the current research indicate that the security community, having passed through two different generations of theorizing the concept of security community, has a rare capacity for conceptual and theoretical development in the form of an "international theory on security community".